The Effect of Pressure on the Dissolution of Cellulose in Ionic Liquids - Ibrahim, Mohamed Farouk (Universiti Teknologi PETRONAS, 2013)
The dissolution of cellulose in ionic liquids allows the comprehensive application of cellulose by combining two major green chemistry principles, which is by using bio-renewable feed-stocks and environmentally friendly solvents. In previous study by Rogers and co-workers, the dissolution of cellulose in ionic liquids required high temperature and high energy consumption. To overcome the high energy and temperature needed for dissolution, an idea was tinkled to conduct the dissolution in a pressurized cell. In this paper, the main objective is to study the pressure effect on the dissolution of cellulose in ionic liquids. Throughout the study, the pressure and temperature on dissolution of cellulose in ionic liquids were varied. The dissolution process were observed, the sample was later analysed with microscope and the dissolution time was taken. The controlling and varying value of the pressure and temperature significantly affect the dissolution time of cellulose. In this thesis, the findings show that as the pressure increase, the dissolution time decreases. The temperature also showed same behaviour, as the temperature increases, the dissolution time decreases. In conclusion, pressure does effects the dissolution rate and lower down the energy consumption for dissolution of cellulose in ionic liquids.